Asuhan Keperawatan pada Pasien yang Mengalami Nyeri Akut dengan Post Operasi Atas Indikasi Mioma Uteri di RSUD dr. Chasbullah Abdulmadjid Kota Bekasi - Zakiyyah, Dhiya Luthfi; Agustina, Agustina; Veronica, Rina (STIKes Persada Husada Indonesia, 2024)
Uterine myoma, also called leiomyoma, fibromyoma, or fibroid, is a benign neoplasm that originates from the uterine muscle and connective tissue. This study aims to obtain an overview of the implementation of nursing care for patients experiencing acute post-operative pain for indications of uterine myoma at RSUD Dr. Chasbullah Abdulmajid Bekasi City in 2024. The incidence of uterine myoma is around 60-75% occurring in women aged over 20-35 years of all women in the world and continues to increase. Data results from medical records at RSUD Dr. Chasbullah Abdulmajid stated that the number of uterine myoma patients in 2023 will be 78 cases. From the nursing care carried out, it was found that the priority nursing diagnosis for client 1 was acute pain related to a physiological injury agent. In client 2, a priority nursing diagnosis was found, namely acute pain related to a physical injurious agent. The implementation that has been carried out to overcome the priority problem of acute pain in both clients is collaboration with doctors in administering analgesic drugs. At the evaluation stage, the two clients' nursing problems were unresolved and unresolved. So, it is recommended for nurses to continue implementing unsolved nursing problems experienced by clients.